Proactive personality and positional competition: exploring the impact on soccer players` performance and gender differences - Çar, B.; Kurtoglu, A.; Eken, Ö.; Sufaru, C.; Ciaccioni, S.; Baskaya, G.; Panaet, E. A:; Dragomir, L.; Alexe, C. I.; Bulzan, C. O. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Aim The study aims to explore the relationship between proactive personality and positional competition in soccer players, considering factors like gender, age, position, and years of active participation in the sport.